The Impact of Current Immunosuppression Strategies in Renal Transplantation on the Field of Reconstructive Transplantation - Chang, Jeff; Davis, Connie L.; Mathes, David W. (Journal of Reconstructive Microsurgery, 2012)
Composite tissue allograft (CTA) transplantation, such as the clinical face and hand transplants, has now been performed in multiple centers across the world. The transplants have successfully treated complex injuries that have either failed conventional approaches or where autologous reconstruction could not restore both form and function. CTA transplantation has the potential to improve outcomes over traditional techniques. However, the widespread application of CTA transplantation continues to be limited by the need for chronic immunosuppression. Due to the small numbers of CTA transplants performed, any modification in the immunosuppression used will likely be based from the solid organ literature. The renal transplantation literature has served as the basis for the current selection of CTA drug regimens and in this article we review the evidence in the renal transplant literature for the selection of immunosuppressive regimens. The study then compares the regimens used in both the face and hand transplantation with those regimens currently used for renal transplantation.
Keywords: Immunosuppression; composite tissue allotransplantation; face transplantation